Analysis of microbial community and its correlation with flavor compounds during Congee fermentation. (February 2023) - Yang, Yang; Wu, You Na; Ce, Li Ge Er; Ge, Xi Ge Bu Ren; Shuang, Quan; Zhang, Feng Mei
Abstract: We investigated the structural changes in the microbial flora during the fermentation process (with primers added for fermentation) of Congee and its influence on the flavor compounds of Congee using high-throughput sequencing technology. W detected and analyzed the bacterial and fungal community dynamics. In addition, gas chromatography–mass spectrometry, electronic nose technology, and electronic tongue technology were used to monitor the changes in the flavor compounds of Congee at different fermentation time points; the correlation between the two was analyzed. The Illumina MiSeq sequencing showed bacterial in Congee samples at different fermentation stages belonged mainly to genera Lactobacillus, Kosakonia, and Enterococcus . The major fungal genera were Yarrowia, Dipodascus, and Pichia. Gas chromatography–mass spectrometry (GC-MS) revealed that 90 volatile compounds were detected in the Congee samples during the fermentation process, among which ethyl acetate, eucalyptol, nonanal, heptyl ethyl acid, and acetic acid constituted important aroma compounds in Congee. In addition, 16 amino acids were detected from the Congee samples. At 48 h of fermentation, the content of total amino acids increased to twice that at 0 h of fermentation; the contents of glutamic acid and aspartic acid were the highest. The electronic nose technology revealed that the W5S (nitrogen oxide), W1S (methyl) and W1W (sulfide sensitive) sensors showed a higher response to Congee samples. In terms of taste, the response signals of Congee, sweetness, and saltiness were the strongest. The covariance between microbial flora and flavor compounds was analyzed by Spearman's correlation analysis. Ralstonia was significantly positive correlation with found with pyridine, butanoic acid, hexanoic acid, and D-limonene ( p < 0.05), and a significant negative correlation with hexadecanoic acid and ethyl ester ( p < 0.05). Bacillus exerted a significant positive correlation with heptanoic acid and ethyl ester ( p < 0.05). Yarrowia was positively correlated with compounds such as heptanoic acid, ethyl ester, ethyl 2-methyl butyrate ( p < 0.05) and negatively correlated with 2-Dece0l, (E)-, Hepta0l ( p < 0.05). Dipodascus was negatively correlated with compounds such as naphthalene, furan, 2-pentyl-, butanedioic acid ( p < 0.05). In all, Ralstonia, Bacillus, Yarrowia, and Dipodascus exerted positive effects on the formation of the Congee flavor.